2019
DOI: 10.3389/fphys.2018.01952
|View full text |Cite
|
Sign up to set email alerts
|

Diurnally Fluctuating pCO2 Modifies the Physiological Responses of Coral Recruits Under Ocean Acidification

Abstract: Diurnal pCO2 fluctuations have the potential to modulate the biological impact of ocean acidification (OA) on reef calcifiers, yet little is known about the physiological and biochemical responses of scleractinian corals to fluctuating carbonate chemistry under OA. Here, we exposed newly settled Pocillopora damicornis for 7 days to ambient pCO2, steady and elevated pCO2 (stable OA) and diurnally fluctuating pCO2 under future OA scenario (fluctuating OA). We measured the photo-physiology, growth (lateral growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…Indeed, while OA has been shown to be detrimental to adult coral colonies (see above), contrasting responses have been observed in young recruits and larvae. For example, Jiang et al (2019Jiang et al ( , 2020 found a positive photochemical response to OA along with enhanced symbiont CCMs in Pocillopora recruits and greater productivity in larvae. Finally, parabolic responses of photosynthetic processes to acidification stress have also been documented (Crawley et al, 2010;Castillo et al, 2014).…”
Section: Responses Of Coral Holobionts To Oa Vary Greatlymentioning
confidence: 99%
“…Indeed, while OA has been shown to be detrimental to adult coral colonies (see above), contrasting responses have been observed in young recruits and larvae. For example, Jiang et al (2019Jiang et al ( , 2020 found a positive photochemical response to OA along with enhanced symbiont CCMs in Pocillopora recruits and greater productivity in larvae. Finally, parabolic responses of photosynthetic processes to acidification stress have also been documented (Crawley et al, 2010;Castillo et al, 2014).…”
Section: Responses Of Coral Holobionts To Oa Vary Greatlymentioning
confidence: 99%
“…In particular, the transcript level of pk in HCd-treated copepods was markedly upregulated under steady OA versus ambient p CO 2 exposure, whereas the transcription of hk1a and pk and the ATP content were significantly higher at LCd or HCd exposure under fluctuating OA conditions in contrast to steady OA (Figure c,d). Previous studies illustrate that both fluctuatingly high p CO 2 , and Cd exposures can enable marine organisms to alter energy expenditure on regulating their physiological responses under such stress. Significant synergism between p CO 2 and Cd indicated that higher energy was available for detoxification defense and stress response in Cd-treated copepods under fluctuating versus steady OA.…”
Section: Resultsmentioning
confidence: 99%
“…The steady p CO 2 levels of 400 and 1000 μatm were used to represent the current condition and the predicted value for the year 2100 under RCP8.5, respectively . The fluctuating p CO 2 level of 1000 ± 600 μatm was created by superimposing the current diurnal variance on the predicted p CO 2 level for 2100 . Briefly, the fluctuating acidification treatment was conducted by changing the seawater p CO 2 every 6 h; in particular, it was designated as 1000, 400, 1000, and 1600 μatm at 07:00, 13:00, 19:00, and 01:00, respectively, based on the diurnal cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Exposure to (naturally) fluctuating low pH conditions can have very different effects to those in constant pH reductions (e.g. Onitsuka et al, 2018;Jiang et al, 2019). Thus, it is possible that the integrated effects of frequent peaks of low pH have a stronger impact than that computed with the mean at lower frequency.…”
Section: Discussionmentioning
confidence: 99%